Morphologies of spherical polyampholyte brushes: Effects of counterion valence and charged monomer sequence. (24th March 2017) - Cao, Qianqian; You, Hao
Abstract: We study the conformational behavior of spherical brushes composed of polyampholyte chains end-grafted onto spherical particles in the presence of monovalent and tetravalent counterions using molecular dynamics simulations. The overall net charge for each chain consisting of both positively and negatively charged segments is zero. The dependences of the structural properties of the brushes on the chain stiffness, grafting density and charge sequence along the chains are examined systemically. For the diblock brushes, our results indicate that increasing the chain rigidity leads to a significant effect of counterion valence and a reduced collapsing degree of the brushes. At high chain stiffness, the number of high-valent counterions trapped in the brushes is diminished compared to the cases with monovalent counterions, corresponding to lower osmotic pressure. For the flexible brushes, the short-range and electrostatic interactions depending on the charge sequence, determine the conformational transition of the brushes, whereas the effect of counterion valence becomes weaker. In the presence of high-valent counterions, the brushes which consist of polyampholyte chains with blocks of medium length, adopt a slightly stretched conformation owing to relatively strong electrostatic correlation between high-valent counterions and oppositely charged monomers. Graphical abstract: Highlights: The effect of counterion valence becomes more significant with increasing the chain stiffness. A remarkable reduction of highvalent counterions within the brush and concomitantly reduced osmotic pressure at high chain stiffness were identified. For the flexible brushes, the conformational transition related to the charge sequence depends on the shortrange and electrostatic interactions.